Psychophysical health and perception of well-being between master badminton athletes and the adult Italian population. - Lassandro, Giuseppe; Trisciuzzi, Rodrigo; Palladino, Valentina; Carriero, Francesco; Giannico, Orazio Valerio; Tafuri, Silvio; Valente, Roberto; Gianfelici, Antonio; Accettura, Domenico; Giordano, Paola (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Sport participation, regular exercise and physical activity in general exert many benefits on wellness, perceived health related quality of life and social satisfaction. As the people age, physical and mental deterioration occur. Master athletes are older adults that practice different sports, such as running, swimming and badminton. This is a widespread sport practiced by over 200 million people and is one of the most exerted sport in the world. In our study we compared the health perception of Italian Badminton Master athletes and normal Italian population of same age. Methods: Thirty (22 males, 8 females) Master badminton athletes between 18 and 69 years old participating to 2018 edition of the Italian Master Badminton Championship were enrolled for the study. All athletes compiled a six questions questionnaire, about perceived quality of life, included in the 2014-2017 Italian surveillance database “PASSI” questionnaire and answers were compared to 18-69 y/o Italian population results included in the public database. Results: Statistically significative differences were not detected between genders of master athletes. There was only a significative better psychological perception of quality of life in younger class of master athletes (p<0.05). A significative better perception was detected in Master athletes compared to normal Italian population. Conclusions: Aerobic sports, such as badminton, represent positive factors for improving health, psychological wellness and social engagement. Sport has a crucial role for the positive influence on growth in youngers and on the preventive role on typical diseases of older age, such as diabetes, ischemic cardiomyopathy and mental illness.